(untitled) (Encuentros, 2022)
The main objective of the study was to analyze the change in the conceptions that future mathematics teachers (FPM) have regarding the design of tasks that promote argumentation in mathematics classes in an initial training course. The qualitative methodology and guided by the educational design research approach (DBR), was situated in the methodology of the implementation of the research to carry out a questionnaire at the beginning and a mathematical task design activity at the end of the course. The study’s main results show the change in the conceptions of the FPM and the varied proposals of mathematical task designs that involved exploration and argumentation activities. We conclude that the implementation of the research results generated awareness in the participants regarding how the results of research in Mathematics Education contribute to the improvement of the mathematics teaching process.